Edukasi Dampak Bullying bagi Remaja melalui Pendidikan Kesehatan di SMK Harapan Bersama Kota Tegal - Evi Zulfiana; Ratih Sakti Prastiwi; Istiqomah Dwi Andari; Vivin Avianti Oktavia; Seventina Nurul Hidayah; Nora Rahmanindar; Asa Roudhotul Jannah; Liza Luthfia Permana (Jurnal Surya Masyarakat, 2024)
Adolescence is a phase of development between childhood and adulthood. Where at this time adolescents have emotional, social, physical and psychological maturity. Adolescents have developmental stages that must be passed with various difficulties. The reality in the field is that there are still many adolescent students who unconsciously commit acts of bullying against their own friends, so education on the impact of bullying is very important to prevent bullying in adolescents. The solution to prevent and overcome this problem is with Community Service Activities in the form of providing health education, the purpose of this service is to increase knowledge about bullying, the activities carried out are by providing a pre-test before providing material to find out the knowledge of students, then providing bullying materials, the first step taken is to provide pre-test and post-test,  the implementation of service on January 11-12, 2024 at Harapan Bersama Vocational High School with the city of Tegal on 40 students, The results of the post-test showed an increase in knowledge about bullying so that it can be concluded that there is an increase in knowledge of bullying in female students.